PELATIHAN PEMBUATAN ALAT PERMAINAN EDUKATIF (APE) BERBAHAN LIMBAH RUMAH TANGGA DI TK DHARMA WANITA TUNAS HARAPAN DESA GEBANGMALANG - Jazilah, Khoirul; Nuraini, Mardiana (Amaliyatu Tadris, 2023)
The problems that arise in the Dharma Wanita Tunas Harapan Kindergarten educators in Gebangmalang Village, one of which is competence. In developing the Educational Game Tool (APE) by utilizing the materials around it. This service activity aims to improve the competence of educators of the Dharma Wanita Tunas Harapan Kindergarten which is focused on the abilities and skills of educators in designing and making APE for the learning of students of Dharma Wanita Tunas Harapan Kindergarten in Gebangmalang Village by utilizing household waste that is suitable for use. The development of educational game tools (APE) by utilizing household waste that is suitable for use will be able to minimize the costs that must be incurred by educational institutions in implementing learning at Dharma Wanita Tunas Harapan Kindergarten. The evaluation results show that the material is in accordance with the learning needs of the training participants and the final results of the training are as expected, this can be seen from the results of the evaluation that has been carried out during the training process..